STRATEGI DAN RENCANA BISNIS WOOWEDU DALAM EKOSISTEM BISNIS PRODUK DIGITAL TEKNOLOGI PENDIDIKAN DI INDONESIA - Junius, Roy Stevanus; Prabantoro, Gatot (Universitas Ichsan Sidenreng Rappang, 2025)
This study explores the WoowEdu platform as an innovative digital learning solution in the Indonesian education sector. The objective is to analyze WoowEdu's strategic role in addressing educational challenges such as limited access, inconsistent teaching quality, and the need for an integrated learning system. Using a descriptive qualitative approach with a case study method, this study employed strategic analysis tools including SWOT, TOWS Matrix, and Porter's Generic Strategies to evaluate WoowEdu's business position. Data collection was conducted through observation, interviews, and documentation involving stakeholders such as teachers, students, principals, and parents. The research findings indicate that WoowEdu offers a comprehensive Learning Management System (LMS) that supports the planning, implementation, and evaluation of learning activities. Its features—ranging from material management and assessment to parental monitoring and collaborative tools—improve operational efficiency, learning quality, and stakeholder engagement. The platform facilitates both synchronous and asynchronous learning, enabling flexible access and encouraging creative thinking among students. The evaluation results indicate that WoowEdu contributes positively to learning outcomes and the development of digital competencies. The study concludes that WoowEdu is not only a technological tool but also a strategic catalyst for improving the quality and inclusiveness of education in the digital era.